Efficiency analysis of Italian wine producers - Arturo Urso; Giuseppe Timpanaro; Francesco Caracciolo; Luigi Cembalo (Wine Economics and Policy, 2018)
An analysis of the efficiency of wine and grapevine producers in Italy was performed. Data for 2005 and 2010 from the Farm Accountancy Data Network were used; this network records the balance sheets of a representative sample of farms. The data were analyzed using data envelopment analysis, which is a method for estimating the comparative efficiency of a group of farms. We investigated the determinants of the estimated levels of efficiency through an econometric model, aiming to understand which farm and area characteristics affect the differences in efficiency levels. The results indicate that between 2005 and 2010, a reduction in grape prices led to an increase in the efficiency of companies producing wine compared with a significant reduction among companies that are dedicated exclusively to the production of grapes.
Keywords: 330; Data envelopment analysis; Italian wine and grapevine production; Tobit model